Role of digital education through smartphones in improving knowledge among asthma patients: A preliminary study - Pohan, Indah TS.; Tarigan, Amira P.; Pandia, Pandiaman; Mutiara, Erna (Narra J, 2024)
Asthma is a chronic inflammatory airway disorder and is among the top ten causes of morbidity and mortality in Indonesia, highlighting the need for effective management strategies. This study aimed to evaluate changes in asthma knowledge levels before and after using the "Paru Sehat" smartphone application for digital education. A quasi-experimental study using a pre- and post-test design was conducted over three months at the outpatient clinic of Universitas Sumatera Utara Hospital, Medan, Indonesia, among asthma patients aged over 18 years. The patients completed the Patient Asthma Knowledge Questionnaire (PAKQ) before installing the "Paru Sehat" application to establish baseline knowledge. Once a week, patients received reminders to access materials covering an asthma overview, peak flow meter use, medication differences, and management techniques. After four weeks of intervention, the participants' knowledge was reassessed using the PAKQ. Data were analyzed using either paired Student's t-test or Wilcoxon test to assess the improvement in knowledge. The results showed increases in knowledge about asthma in general, asthma triggers, and asthma diagnosis domains, with the median score in each domain rising by one point (p=0.003, p=0.001, and p=0.002, respectively). The asthma management domain exhibited the largest change, with a median increase of two points (p<0.001). The total scores increased by an average of five points (p<0.001), indicating an overall improvement in patient knowledge about asthma. The "Paru Sehat" application demonstrated significant potential in enhancing asthma knowledge across multiple domains. Further research is warranted to explore the long-term effectiveness of the application in diverse populations and settings, ultimately contributing to improved asthma management and patient outcomes.